Ameliorative Potential of Cymbopogon citratus Decoctions on Gasoline Vapour-Induced Nephrotoxicity - E. Ekpenyong, Christopher; S. Akpan, Nsuhoridem (Natural Products Journal, The, 2017)
Background: Gasoline is a mixture of several hydrocarbons and additives and is associated with numerous adverse health effects including renal function impairment. The aim of this study was to evaluate the ameliorative effect of Cymbopogon citratus on gasoline vapour-induced renal function impairment. Methods: Seventy-two mature female Wistar albino rats were divided in-to six groups (n = 12 per group). Group (G1) was the control group; G2 was exposed to gasoline vapour alone; G3, G4, and G5 were exposed to gasoline vapour and co-administered 500 mg/kg, 1000 mg/kg, and 1500 mg/kg C. citratus, respectively; and G6 was exposed to gasoline vapour and co-administered 200 mg/kg vitamin C. After 35 days of treatment, the animals were sacrificed, and blood was obtained for biochemical analysis. Nephrotoxicity was evaluated by measuring serum levels of the renal biochemical parameters creatinine (Cr), urea (Ur), glucose (Glu), uric acid (UA), sodium (Na+), potassium (K+), bicarbonate (HCO3 -), and chloride (Cl-). Gasoline vapour-induced nephrotoxicity was confirmed by histopathological examination of the kidney sections. Results: Results showed significant (p<0.05) increases in the levels of serum renal biochemical and hismorphological profile in animals exposed to gasoline alone (G2) compared to the levels in control animals (G1). However, when Cymbopogon citratus decoction was co-administered, these increases in renal parameters were dose-dependently reversed. Similar changes were observed in vitamin Ctreated animals. Conclusion: The results suggest the ameliorative effect of Cymbopogon citratus on gasoline vapourinduced nephrotoxicity. The ameliorative effect was evident through improvement of the biochemical and histopathological markers of nephrotoxicity. The changes observed in malonaldehyde suggest that the ameliorative effect of Cymbopogon citratus might be attributable to the antioxidant activity of its bioactive constituents.
Keywords: Hydrocarbon